2003
DOI: 10.1590/s0103-90162003000200025
|View full text |Cite
|
Sign up to set email alerts
|

Practical method for germination of Araucaria angustifolia (Bert.) O. Ktze. seeds

Abstract: The germination of seeds of Araucaria angustifolia (Brazilian Pine) is generally a slow and fastidious process that causes loss of many seeds because of the incidence of pathogens. The objective of this study was to evaluate whether seeds with cut edges present greater germination percentages or precocity when compared to untreated, normal seeds. The experimental design was completely randomized design with 100 pre-cut and 100 non-treated seeds. The experiment was installed twice, in 1998 and 1999, from fresh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 4 publications
(6 reference statements)
3
7
0
3
Order By: Relevance
“…Seeds were surfacedecontaminated with sodium hypochlorite solution (2 %, v/v) for three minutes, and subsequently the tip of each seed was cut off at approximately 3 mm (Moreira-Souza & Cardoso, 2003). Four replications of 25 seeds each were sown in trays with vermiculite, and placed in a germination chamber at 25 °C, with photoperiod of 12 hours.…”
Section: Germination Testmentioning
confidence: 99%
“…Seeds were surfacedecontaminated with sodium hypochlorite solution (2 %, v/v) for three minutes, and subsequently the tip of each seed was cut off at approximately 3 mm (Moreira-Souza & Cardoso, 2003). Four replications of 25 seeds each were sown in trays with vermiculite, and placed in a germination chamber at 25 °C, with photoperiod of 12 hours.…”
Section: Germination Testmentioning
confidence: 99%
“…Plagiotropism in araucaria is also a great challenge that needs to be overcome (OLIVEIRA, 2010;WENDLING, 2011). For example, it has been observed that rooted cuttings of primary branches still had horizontal growth four years after planting (OLIVEIRA, 2010), preventing the development of normal plants.…”
Section: Figura 4 -Sobrevivência Na Saída Da Casa De Vegetação (A) Cmentioning
confidence: 99%
“…For example, it has been observed that rooted cuttings of primary branches still had horizontal growth four years after planting (OLIVEIRA, 2010), preventing the development of normal plants.…”
Section: Figura 4 -Sobrevivência Na Saída Da Casa De Vegetação (A) Cmentioning
confidence: 99%
See 1 more Smart Citation
“…As avaliações de plântulas normais foram realizadas a cada três dias para o cálculo do índice de velocidade de germinação (IVG) até o período de 64 dias após o início do teste de germinação, respeitando-se a expressão do máximo potencial germinativo das sementes. Os períodos de 60 e 70 dias após o início do teste de germinação foram considerados por outros autores para a análise dos resultados de plântulas normais em sementes de A. angustifolia, quando há a máxima germinação (Moreira-Souza & Cardoso, 2003;Garcia et al, 2014, respectivamente). O critério para avaliação de plântulas normais foi adotado conforme prescrito nas RAS (Brasil, 2009).…”
Section: Introductionunclassified